A decade of cybersecurity research in business, management, and accounting: bibliometric analyses and future research directions - Wasim Al-Shattarat; Kameleddine B. Benameur; Mohamed M. Mostafa; Ahmed Hassanein; Ruba Subhi Hamed (Cogent Business & Management)
This study bridges the gap and maps the evolution of cybersecurity research in business, management, and accounting over the past decade from 2012 to 2022. Using a scientometric approach, we analyzed 129 peer-reviewed Scopus articles authored by 334 scholars from 26 countries. We employ bibliometric network analysis, thematic mapping, and keyword co-occurrence techniques to explore citation trends, thematic evolution, and collaboration networks. The results identify leading authors, journals, institutions, and countries and reveal substantial growth in this domain with a projected continued trend. We find evidence of the ‘homophily impact’ among top authors and observe the ‘Matthew effect,’ where a few researchers dominate scholarly networks. Our findings provide a roadmap for future research and offer practical implications for firms and policymakers, shedding light on the role of cybersecurity in business, management, and accounting. This study serves as a valuable reference for scholars aiming to navigate the landscape and identify emerging themes in this rapidly evolving field.